Comparison of urinary vitamin D binding protein with albumin-creatinine ratio in type 2 Diabetes Mellitus as an early screening tool for diabetic nephropathy - Mehmood, Hafiz Muhammad Khalid; Yasmeen, Munazza; Ghaznavi, Sumbla; Waheed, Mr. Abdul; Rasheed, Miss Nadia (Journal of Fatima Jinnah Medical University, 2020)
ABSTRACT Introduction:- Diabetes mellitus (DM) is a group of metabolic disorders. Diabetic nephropathy is one of the chronic complications of DM, leading to End stage renal disease (ESRD). A current diagnostic criterion for diabetic nephropathy is measurement of microalbuminuria, which is 30 to 300 mg of albumin/24 hour’s urine or ratio of albumin to creatinine (ACR) in the range of 30 to 300 mg/g in random urine sample but it shows inadequate sensitivity for the early detection of diabetic nephropathy. Methodology:- This was a comparative cross sectional study, which comprised of seventy five study subjects and were distributed into three study groups with 25 subjects in each group, having age in the range of 40-50 years.Group-1 comprising controls (without diabetes mellitus),Group-2 contained diabetes mellitus patients with normoalbuminuria. Group-3 composed of diabetes mellitus patients with microalbuminuria. Vitamin D binding protein, urine creatinine and albumin was measured from the urine sample of each study subjects. Determination of creatinine in urine was performed by jaffe method and albumin in urine was determined by immunoturbidimetric method. Vitamin D binding protein was measured by ELISA method. Levels of VDBP and albumin were normalized with urine creatinine and expressed as VDBP creatinine ratio as (ng/mg) and albumin creatinine ratio as (mg/g) in the spot urine sample. Results:-Results of this study showed that level of Vitamin D binding protein was significantly increased in diabetes mellitus in comparison to control subjects. Conclusion:- Our results proposes that urinary vitamin D binding protein levels is likely to become a useful biomarker for the early detection of diabetic nephropathy in diabetic patients which can be helpful in early treatment and will help to manage diabetic nephropathy. ABSTRACT Introduction: Diabetes mellitus (DM) is a group of metabolic disorders. Diabetic nephropathy is one of the chronic complications of DM, leading to end stage renal disease (ESRD). A current diagnostic criterion for diabetic nephropathy is measurement of microalbuminuria, which is 30 to 300 mg of albumin/24 hour’s urine or ratio of albumin to creatinine (ACR) in the range of 30 to 300 mg/g in random urine sample but it shows inadequate sensitivity for the early detection of diabetic nephropathy .Current diagnostic criterion for diabetic nephropathy (DN) is detection of microalbuminuria, which is 30 – 300 mg/24 hours of albumin excretion in urine or albumin to creatinine ratio (ACR) in the range of 30 – 300 mg/g in the random urine sample but, it shows inadequate sensitivity for the early detection of DN. It has been observed that increased excretion of UVDBP is related to tubular dysfunction. This protein is excreted in urine earlier than albumin. Hence it can be used as a tool to early detection of DN in type 2 diabetic patients. Methodology: This was a comparative cross sectional study, which comprised of seventy five study subjects and were distributed into three study groups with 25 subjects in each group, having age in the range of 40-50 years. Group-1 comprising controls (without diabetes mellitus), Group-2 had diabetes mellitus with normoalbuminuria while Group-3 comprised of diabetes mellitus patients with microalbuminuria. Vitamin D binding protein, urine creatinine and albumin were measured from the random urine sample preferably early in the morning urine sample of each study subjects using ELISA, Jaffe and immunoturbidimetric methods respectively. Levels of VDBP and albumin were normalized with urine creatinine and expressed as VDBP creatinine ratio as (ng/mg) and albumin creatinine ratio as (mg/g) in the spot urine sample. Results: Urinary VDBP levels among the three groups were as the highest Median, IQR (Q1- Q3) values were observed in group 3 as 1056 ng/mg,(905 ng/mg – 1215 ng/mg) followed by group 2 as 442 ng/mg,(381.50 ng/mg – 523 ng/mg) and group 1 as 98 ng/mg,(73.50 ng/mg – 149 ng/mg) respectively, and a statistical significant difference was observed among the three groups with a p- value of 0.000. Results of this study showed that level of Vitamin D binding protein was significantly increased in diabetes mellitus in comparison to control subjects. Conclusion: Results suggest that urinary vitamin D binding protein level is likely to become a useful biomarker for the early detection and management of diabetic nephropathy in Type 2 diabetic patients.